Development of quadratic sensitivity method in transfer capability computation / Dr. Muhammad Murtadha Othman and Mohd Fuad Abdul Latip - Othman, Muhammad Murtadha (Dr.); Abdul Latip, Mohd Fuad (2007)
In a deregulated electric power industry, transmission providers are required to rapidly produce commercially viable information of accurate available transfer capability (ATC) values so that such information can help power marketers, sellers and buyers in planning, operation and reserving transmission services. Fast and accurate available transfer capability (ATC) methods are required to evaluate the ability of transmission systems to reliably increase power transfer between areas or commercial entities for use in the electricity markets. This report presents a new computationally fast and accurate method for evaluating ATC based on voltage and absolute power sensitivities. The feature of the method is that it formulates the sensitivity factors in the form of second order polynomial equations and the polynomial coefficients are determined so as to avoid the time consuming power flow iterations usually required in the ATC evaluation. Prior to the ATC evaluation, contingency ranking and selection techniques are used to define the critical lines in a system that can adversely affect the transfer capability assessment. The effectiveness of the proposed method is verified by illustrating the ATC evaluation on the Malaysian system and IEEE 9-bus system. ATC results obtained from the proposed quadratic sensitivity method prove that the method is satisfactorily accurate and it is faster than the ATC method using recursive AC power load flow method.